Internal Attempts To Assassinate Egyptian President Hosni Mubarak Between 1993 And 1999: A Reading of The Motives And Repercussions (Journal of the College of Basic Education, 2025)
There were a series of assassination attempts, both internally and externally, targeting Egyptian President Hosni Mubarak, whose reasons and motives varied and left effects on the Egyptian and international reality. During the period between 1993 and 1999, Mubarak was subjected to three internal assassination attempts, two of which were by groups belonging to Islamic organizations, which were known to oppose Mubarak’s regime and were waiting for opportunities to get rid of him. As for the other attempt, it was individual, and there is a mystery surrounding the perpetrator of the operation, whether he belonged to an armed group or whether it was carried out individually?